Realizing Relational Preferences Through Transforming Interpersonal Patterns. Issue 1 (15th December 2018) - Gaete, Joaquín; Sametband, Inés; St. George, Sally; Wulff, Dan; Tomm, Karl; Durán, Gabriela
Abstract : Family therapy has often been conceptualized as a conversational process whereby therapists and clients generate new meanings. Based on a 3‐year study of conversational practices observable in successful family therapy processes of Chilean families with a child/adolescent who is engaged in disruptive behaviors, we looked for clinical examples of Transforming Interpersonal Patterns (TIPs). TIPs are a key aspect of the IPscope, a framework we used to explore the meaning‐making processes in family therapy. TIPs constitute a novel approach to explore therapeutic processes by identifying empirically traceable conversational practices involved in generating "new meanings." TIPs are involved in bringing forth and discursively articulating ("talking‐into‐being") clients' preferred ways of relating and living (i.e., relational preferences or RPs). We analyze conversational data from successful family therapy sessions/treatments, and present an emergent model of five categories of conversational practices making up TIPs, namely: Preparatory TIPs, Identifier TIPs, Tracker TIPs, Transformer TIPs, and Consolidator TIPs . We have called them "realizers" because these conversational practices help families talk‐into‐being (or "make real") particular relational preferences. We also offer user‐friendly descriptors of realizers' subcategories (e.g., Measuring TIPs ) which may help practitioners to recognize, learn, and perform these conversational invitations. Theoretical consequences and future lines of research are discussed. Resumen: La terapia familiar generalmente se ha conceptualizado como un proceso conversacional por medio del cual los terapeutas y los pacientes generan nuevos significados. Basándose en un estudio de tres años de prácticas conversacionales observables en procesos satisfactorios de terapia familiar de familias chilenas con un niño/adolescente que tiene comportamientos disruptivos, buscamos ejemplos clínicos de patrones interpersonales transformadores (PIT). Estos patrones son un aspecto clave del "IPscope" o instrumento de evaluación de los patrones interpersonales (Tomm, St. George, Wulff, & Strong, 2014), un marco que usamos para analizar los procesos de creación de significado en la terapia familiar. Los patrones interpersonales transformadores constituyen un enfoque innovador para analizar los procesos terapéuticos mediante el reconocimiento de prácticas conversacionales fáciles de seguir empíricamente que participan en la generación de "significados nuevos". Los patrones interpersonales transformadores intervienen en la presentación y la articulación discursiva ("convencer de crear") de las manersa preferidas de los pacientes de relacionarse y vivir (p. ej.: preferencias relacionales o PR). Analizamos datos conversacionales de sesiones/tratamientos satisfactorios de terapia familiar y presentamos un modelo emergente de cinco categorías de prácticas conversacionales que constituyen patrones interpersonales transformadores, por ejemplo: PIT preparatorios, PIT identificadores, PIT localizadores, PIT transformadores y PIT consolidadores . Los hemos llamado "realizadores" porque estas prácticas conversacionales ayudan a las familias a convencerlas de crear (o a "hacer realidad") preferencias relacionales particulares. También ofrecemos descriptores fáciles de usar de las subcategorías de los realizadores (p. ej.: PIT de medición) que pueden ayudar a los profesionales a reconocer, aprender y llevar a cabo estas invitaciones conversacionales. Se debaten las consecuencias teóricas y las futuras líneas de investigación. 摘要: 家庭治疗通常被认为是一种会话过程, 通过会话治疗师和来访者共同构建新的意义。本研究基于对一个智利家庭的成功家庭治疗过程中为期三年的会话实践观察, 试图从中寻找变革性人际交往模式(TIPs)的临床案例。参与研究的家庭有一个较多破坏性行为的少年。TIPs是IPscope (Tomm, St. George, Wulff, & Strong, 2014)的一个重要方面, 是我们用于探索家庭治疗中意义构建的过程所使用的一种框架。TIPs是一种新型的治疗方法, 它在治疗过程中辨认区分那些实证性的可追踪的有关生成"新的意义"的会话实践。TIPs有关引导出并靠不断交谈传达出(即多说而成现实)来访者的偏好关联方式和生活方式(即关系偏好)。我们分析了成功的家庭治疗会谈/治疗处理时的交谈数据, 提出五个自然显现出来的会话实践类别:准备TIPs、辨认TIPs、跟踪TIPs、改变TIPs、巩固TIPs。我们称他们为"实现者", 因为这些会话实践帮助家庭谈话中实现(或"变为现实")某种特定的关系偏好。我们也提供对使用者友好的描述词来命名实现者的亚类别(如:测量性TIPs)以帮助行医者辨识、学习和实践这些会话邀请。本文也对理论上的成果和未来研究方向作了讨论。